'Orch OR' is the most complete, and most easily falsifiable theory of consciousness. Issue 2 (3rd April 2021) - Hameroff, Stuart
ABSTRACT: The 'Orch OR' theory attributes consciousness to quantum computations in microtubules inside brain neurons. Quantum computers process information as superpositions of multiple possibilities (quantum bits or qubits) which, in Orch OR, are alternative collective dipole oscillations orchestrated ('Orch') by microtubules. These orchestrated oscillations entangle, compute, and terminate ('collapse of the wavefunction') by Penrose objective reduction ('OR'), resulting in sequences of Orch OR moments with orchestrated conscious experience (metaphorically more like music than computation). Each Orch OR event selects microtubule states which govern neuronal functions. Orch OR has broad explanatory power, and is easily falsifiable.